Cover Feature: Amorphization of Pseudocapacitive T−Nb2O5 Accelerates Lithium Diffusivity as Revealed Using Tunable Isomorphic Architectures (Batteries & Supercaps 6/2022). Issue 6 (13th May 2022) - van den Bergh, Wessel; Wechsler, Sean; Lokupitiya, Hasala Nadeesini; Jarocha, Lauren; Kim, Kwangnam; Chapman, James; Kweon, Kyoung E.; Wood, Brandon C.; Heald, Steve; Stefik, Morgan
Abstract : The Cover Feature shows tailored porous battery architectures being charged with a background reflecting the continuum between crystalline order and disorder. More information can be found in the Research Article by M. Stefik and co‐workers .